1522 Management of Benign Anastomotic Strictures Post-Rectal Resection: A Systematic Review. (12th October 2021) - Manu, N; Clifford, R; Fowler, H; Vimalachandran, D
Abstract: Aim: Approximately a third of all colorectal cancers diagnosed in the UK each year are rectal in origin and will undergo surgical resection with formation of an anastomosis. Focus is placed on techniques to ensure anastomotic integrity however an anastomotic leak, pelvic sepsis, distance to the anal verge and stapler choice are all established risk factors for the formation of a benign anastomotic stricture. This review aimed to assess the use of endoscopic salvage techniques in an attempt to avoid surgical re-intervention. Method: A literature search was performed for published full text articles using the PubMed, Cochrane and Scopus databases. Additional papers were detected by scanning the references of relevant papers. Results: A total of 40 papers were included focusing upon balloon dilation, stent insertion, electroincision, stapler stricturoplasty and corticosteroid use. Endoscopic balloon dilatation remains the most commonly used technique in the management of anastomotic strictures, with a low complication rate despite the frequent requirement for repeated dilatations. Although established in the role for malignant obstruction, stent insertion is yet to gain an established role in the benign setting. Conclusions: Benign anastomotic strictures can be a significant problem post-rectal resection, impacting upon quality of life and requiring repeated intervention. Endoscopic management should be utilised in the primary setting to avoid surgical re-intervention. Standardisation of these methods is imperative in establishing the best modality of treatment. For refractory strictures a low threshold of suspicion for malignant recurrence should be maintained.